Redesign Tampilan Aplikasi IKD Menggunakan Design Thinking dan Evaluasi Menggunakan UEQ - Safitri, Elsa; Pibriana, Desi (Universitas Multi Data Palembang, 2025)
The Digital Population Identity (IKD) application still faces UI/UX problems, such as confusing displays to navigation and inefficient applications for users. This research redesigns the appearance of the IKD application using the Design Thinking method which consists of the Empathize, Define, Ideate, Prototype, and Test stages. Data was collected through interviews and user reviews, then tested using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). The redesign results showed an increase in SUS score from 40 to 79, indicating an improvement in usability from “Poor” to “Good”. All dimensions of the UEQ also improved, indicating an improvement in ease of use and user satisfaction. Thus, the Design Thinking approach proved to be effective in improving the user experience of the IKD application.